Parents vs peers’ influence on teenagers’ Internet addiction and risky online activities - Soh, Patrick Chin-Hooi (2019)
An integral part of the daily lives of adolescents revolves around the Internet. Adolescents are vulnerable online because of a combination of their natural innocence, sensation-seeking drive coupled with the current digital media landscape and its manifold affordances for interactivity, immersive virtual environments and social networking. Adolescence is a time of transition in which youths progressively venture from the safety of the home to explore new opportunities. In this phase of life, both parents and peers play a critical role in either instigating or mitigating risky and dangerous activities. This study examines in the context of youth’s online risky activities, whether the compensatory-competition model or the continuity-cognitive model prevails. This study also explores whether the engagement of parental mediation activities mitigates or compounds the situation. A Partial Least Squares Equation analysis of a stratified random survey of 2000 Malaysian school children between 13 and 15-year-old controlling for age and gender, found that peer-attachment competes with parent attachment for the influence of teenagers’ risky online activities and Internet addiction. Parental influence is stronger when parents actively engage in mediating the online activities of their teenagers. On balance, parents can have more influence on teenagers than their peers.